AN ENERGY-SAVING MATHEMATICAL MODEL IN THE FRAME OF CONFORMABLE DERIVATIVE - BRAIM, HOZHIN MOHAMMED (Fırat Üniveristesi, 2021)
Mevcut araştırmada, bir binanın sıcaklık dinamiklerini modellemek için bazı yerel olmayan tekil kesirli mertebe operatörler kullanılmıştır. Günlük durumlarda komuta yeri olan bu modeli analiz etmek için. Uyumlu türevi ve 0 <? <1 olan ? derecesinin integralini kullanıyoruz. Önerilen modelin çözümünü elde etmek için uyumlu türevin Laplace dönüşümü kullanılmıştır. Bahsi geçen modelin tamsayı olmayan farklı parametrelere sahip olması, binalar için maksimum enerji verimliliğine yaklaşmamıza yardımcı olması, onu değerli kılan en önemli özelliklerinden biridir. Ayrıca tezde amacımız doğrultusunda çözüm eğrisinin hareketliliğini gözlemlemek için simülasyon analizi yapılmaktadır.

In the current research, some non-local singular fractional-order operators are used to model the temperature dynamics of a building. In order to analyze this model, which has a commanding place in daily situations. We utilize conformable derivative and integral of order ? which 0 <?<1. Laplace transform of conformable derivative is employed for obtaining the solution of the proposed model. The fact that the aforementioned model has different non-integer parameters helps us to approach maximum energy efficiency for buildings is one of the most prominent features that makes it valuable. Moreover, in thesis simulation analysis is carried out to observe the mobility of the solution curve in line with our objective..
Uyumlu türev ile enerji tasarrufu sağlayan matematiksel bir model
Keywords: Matematik